Conoscenza e democrazia nelle scelte di giustizia: un’introduzione - DE LEONARDIS, CARLA (Ediesse, 2009)
These notes present and discuss the theoretical and research background of the artiche included in this Section of the Journal. The research carried out on the European activation policies being developed in Amartya Sen’s perspective (in the frame work of the European project “Capright”) provides the analytical feld for exploring the knowledge and information bases of these politices, and for higlighting their normative dimension. The conceptual frame work of the research on Sen’s “informational basis of judgment in justice” is sketched out, and several crucial questions on the connections between knowledge and democracy are raised and discussed. If and how the “capability for voice” of citizens –and particularly of recipient-citizens – counts in the processes of public knowledge bulding and enacting, proves to be a focal point to inquiring whether democracy is being nourished or enganged in these processes